The effects of ketamine on prefrontal glutamate neurotransmission in healthy and depressed subjects - Abdallah, Chadi G; De Feyter, Henk M; Averill, Lynnette A; Jiang, Lihong; Averill, Christopher L; Chowdhury, Golam M I; Purohit, Prerana; de Graaf, Robin A; Esterlis, Irina; Juchem, Christoph; Pittman, Brian P; Krystal, John H; et al. (Neuropsychopharmacology (New York, N.Y.), 2018)
The ability of ketamine administration to activate prefrontal glutamate neurotransmission is thought to be a key mechanism contributing to its transient psychotomimetic effects and its delayed and sustained antidepressant effects. Rodent studies employing carbon-13 magnetic resonance spectroscopy ( C MRS) methods have shown ketamine and other N-methyl-D-aspartate (NMDA) receptor antagonists to transiently increase measures reflecting glutamate-glutamine cycling and glutamate neurotransmission in the frontal cortex. However, there are not yet direct measures of glutamate neurotransmission in vivo in humans to support these hypotheses. The current first-level pilot study employed a novel prefrontal C MRS approach similar to that used in the rodent studies for direct measurement of ketamine effects on glutamate-glutamine cycling. Twenty-one participants (14 healthy and 7 depressed) completed two C MRS scans during infusion of normal saline or subanesthetic doses of ketamine. Compared to placebo, ketamine increased prefrontal glutamate-glutamine cycling, as indicated by a 13% increase in C glutamine enrichment (t = 2.4, p = 0.02). We found no evidence of ketamine effects on oxidative energy production, as reflected by C glutamate enrichment. During ketamine infusion, the ratio of C glutamate/glutamine enrichments, a putative measure of neurotransmission strength, was correlated with the Clinician-Administered Dissociative States Scale (r = -0.54, p = 0.048). These findings provide the most direct evidence in humans to date that ketamine increases glutamate release in the prefrontal cortex, a mechanism previously linked to schizophrenia pathophysiology and implicated in the induction of rapid antidepressant effects.